THE PICTURE OF DORIAN GRAY: A METAPHOR FOR INDIVIDUALS AND FEMALE BODIES THROUGH THE USE OF BEAUTY FILTERS. - da Silva Araújo, Karla Andressa; Teixeira de Brito, João Luiz (Revista de Letras, 2024)
This study uses The Picture of Dorian Gray (WILDE, 1891) as a metaphor to explore the relationship between individuals and female bodies through the use of beautifying filters in Instagram stories. The research is grounded in a literature review that examines the relentless pursuit of youth and beauty, as well as their impacts on Dorian Gray's life. The characters Dorian, Lord Henry, and Basil Hallward are analyzed as archetypes to identify parallels between the quest for an idealized image on digital platforms and the themes presented in Wilde's work. The study invites a reflection on how these filters create an illusion of perfection, reinforcing unattainable beauty standards, and questions whether they pose a threat to individuals. It also investigates the dynamics of seduction and distortion in the relationship between Dorian and Lord Henry. Wilde’s work is interpreted as a metaphor for understanding contemporary dynamics related to self-image and the female body in the age of social media, emphasizing the necessity for critical reflection on the influence of beauty filters in shaping both online and offline identities. Dialogues with scholars such as Lotman (1996), Cintra (2020), Lipovetsky (2015), and Hall (2011) are incorporated to enrich the analysis.